Developing Students 'Information Literature Skill Through The Application of Learning Discovery Learning Model in Social Studies Learning - Aziz, Rahman Abdul (Universitas Pendidikan Indonesia, 2018)
This research is motivated by the problems that occurred in class VII-C 26 Bandung Junior High School that is the low skills of students information literacy in social studies learning. It could seen by still low of student information searching there is only a few students in the group who actively seek information and write it in the task book or worksheet student activity while other group members only see his friends who do the task. In addition, when given the task to seek information in the form of articles the result there are still students who only get information without regarding where they get the information source and then without summarize it is first to make it becomes more effective information. Seeing these problems it is necessary to make improvements in social studies learning that makes students have the skills in identifying, seeking, processing, analyzing, evaluating and communicating information on social studies learning. This research uses Classroom action Research with Kemmis Taggart model design which consists of planning, acting observing and reflecting and is done in four cycles. Researchers try to apply discovery learning model in social studies learning to develop students' information literacy skills. The expected achievement is illustrated on improving the literacy skills of information based on the indicators in the observation guidelines. The success of this research is seen from the improvement of students' information literacy skills shown through the development of several aspects or indicators of information literacy skills such as wanting to find unfinished information submitted by teachers, identifying issues relevant to lessons, organizing information source search strategies, linking various information so that it becomes solutive information, communicating the information findings and makes conclusions based on the information obtained. The most perceived obstacle in this research is the difficulty of organizing and disciplining students when doing observation activities in learning activities. The results of this study indicate that the skills of student information literacy can be developed or improved through the application of the discovery learning model with a very effective in learning social studies.